2020
DOI: 10.25048/tudod.685181
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinde Beden Kütle İndeksi, Tükenmişlik Düzeyi ve İyilik Hâli Arasındaki İlişkinin İncelenmesi

Abstract: Aim: To examine the impact of body mass index (BMI) of university students on burnout levels and wellness. Material and Methods: In the study, 953 university students were enrolled. 'Personal Information Form', 'Maslach Burnout Inventory-Student Survey' and 'Wellness Scale' were the instruments of the study. Ethical approvals were received for the study. In this study, the data were analyzed using the SPSS 21 package program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
1
2
0
1
Order By: Relevance
“…In this study, the majority of the students were found to have normal BMI levels. Similarly, Öcalan et al found that 79% of university students had normal BMI levels [31]. This may be due to the high awareness and knowledge level of the students in our study due to nutrition education.…”
Section: Discussionsupporting
confidence: 63%
“…In this study, the majority of the students were found to have normal BMI levels. Similarly, Öcalan et al found that 79% of university students had normal BMI levels [31]. This may be due to the high awareness and knowledge level of the students in our study due to nutrition education.…”
Section: Discussionsupporting
confidence: 63%
“…The mean BMI of the university students participating in this study was within the normal range, and it was found to be higher for male students. Similarly, Öcalan et al [40] recently found that most university students had normal BMI values. In another cross-sectional study conducted by McCarthy et al [41], BMI values were found to be higher among male university students.…”
Section: Discussionmentioning
confidence: 79%
“…When the results were examined, it was found that as the "DERS-16 Total" score of DERS-16 increased, there was a 17.9% increase in BMI values, a 10.9% decrease in the "Obesity Anxiety" subfactor score of EAT-40, a 14.4% decrease in the "preoccupation with thinness" sub-factor score and a 7.3% decrease in the "EAT-40 Total" score (Table 4). It was found that there was a significant positive and very weak (s = 0.174; p < 0.05) correlation between BMI values and the "Social Pressure" sub-factor score of EAT- 40 and "EAT-40 Total" score (s = 0.174; p < 0.05). When the results were examined, it was found that as the BMI values increased, there was a 27.7% increase in the "Social Pressure" sub-factor score of EAT-40 and a 17.4% increase in the "EAT-40 Total" score (Table 4).…”
Section: Resultsmentioning
confidence: 97%
“…Beslenme ve psikoloji arasında karşılıklı bir ilişki bulunmaktadır (49). Sağlıklı ve dengeli beslenmek, beyin fonksiyonlarını ve hormon dengesini destekleyerek ruh sağlığını olumlu etkiler (39,50).…”
Section: Hakemlik Süreciunclassified